Plasma interleukin responses as predictors of outcome stratification in patients after major trauma: a prospective observational two centre study - Jones, Matthew Allan; Hanison, James; Apreutesei, Renata; Allarakia, Basmah; Namvar, Sara; Ramaswamy, Deepa Shruthi; Horner, Daniel; Smyth, Lucy; Body, Richard; Columb, Malachy; Nirmalan, Mahesan; Nirmalan, Niroshini (Frontiers in Immunology, 2023)
There is a need to develop objective risk stratification tools to define efficient care pathways for trauma patients. Biomarker-based point-of-care testing may strengthen existing clinical tools currently available for this purpose. The dysregulation of pro- and anti-inflammatory cytokines in the pathogenesis of organ failure is well recognised. This study was carried out to evaluate whether blood concentrations of IL-6, IL-10, and IL-6:IL-10 ratios in the early stages of the illness are significantly different in patients with worsening organ function. In this prospective observational cohort study, plasma concentrations of IL-6 and IL-10 on days 1, 3 and 5 were measured in 91 major trauma patients using a multiplexed cytometric bead array approach. A composite measure of adverse outcome - defined as SOFA ≥2 or mortality at 7 days, was the primary outcome. IL-6 and IL-10 concentrations in early samples (days 1, 3 & 5) in patients who developed SOFA ≥2 on day 7 were compared against those who did not. Similar composite outcomes at day 5 and in groups with worsening or improving SOFA scores (ΔSOFA) at days 7 and 5 were undertaken as secondary analyses. Stratification on day 7, 44 (48%) patients showed adverse outcomes. These adverse outcomes were associated with significantly greater IL-6 concentrations on days 1 and 5 (Day 1: 47.65 [23.24-78.68] Vs 73.69 [39.93-118.07]pg/mL, P=0.040 and Day 5: 12.85 [5.80-19.51] Vs 28.90 [8.78-74.08]pg/mL; P=0.0019). Similarly, IL-10 levels were significantly greater in the adverse outcome group on days 3 and 5 (Day 3: 2.54 [1.76-3.19] Vs 3.16 [2.68-4.21]pg/mL; P=0.044 and Day 5: 2.03 [1.65-2.55] Vs 2.90 [2.00-5.06]pg/mL; P<0.001). IL-6 and IL-10 concentrations were also significantly elevated in the adverse outcome groups at day 3 and day 5 when stratified on day 5 outcomes. Both IL-6 and IL-6:IL-10 were found to be significantly elevated on days 1 and 3 when stratified based on ΔSOFA at day 5. This significance was lost when stratified on day 7 scores. Early IL-6 and IL-10 concentrations are significantly greater in patients who develop worsening organ functions downstream. These differences may provide an alternate biomarker-based approach to strengthen risk stratification in trauma patients.